Steroid-sensitive nephrotic syndrome: Do children with early onset of <4 years of age, really need standard therapy? - Kriti Mohan; Mahima Mittal; Manish Kumar; Anchala Bhardwaj (Journal of Family Medicine and Primary Care, 2025)
Background: There are no separate guidelines available for the management of pediatric population with early onset nephrotic syndrome, even if they have difficult disease course. So we conducted this study to analyze the response of the standard steroid regime in these children with early onset (<4 years) steroid-sensitive nephrotic syndrome. Methods: This was a retrospective comparative study with follow-up. Data from children having steroid-sensitive nephrotic syndrome were recorded and divided into two groups: disease onset >1 to ≤4 years of age and disease onset >4 to 10 years of age, and the outcome in these children, treated with standard steroid regimen, was compared. Results: This study included a total of 41 children. Fewer days taken to remission in the first episode, more number of relapses within 6 months of treated first episode, and more number of infection-triggered relapses were significantly associated with the early onset group, while significantly more days were taken to remission in group 2. There was no difference statistically in both cohorts in terms of disease limitation to first episode, no. of mean relapses, cumulative steroid doses, and the need for steroid-sparing agents. Conclusion: More days taken to remission in relapses and more no. of relapses within 6 months of treatment, still no need for increased steroid cumulative doses and steroid-sparing drugs in early onset nephrotic syndrome, defy the need for different therapies or regimes, but in view of significant infection-triggered relapses, role of general hygienic measures, nutrition, and vaccination must be emphasized in these children.